Встреча с прошлым: повесть, рассказы / Т. А. Архипов - Архипов Трофим Архипович (Человек. Писатель. Время, 2005)
Экземпляры: 1 (20170109) / Инвентарный номер: 45172 / Цена: 76.00 / Авт.знак: А 87 / ББК: 84(2Рос=Удм)